CYBER-PHENOMENOLOGY'S VERSION OF NON-FUNGIBLE TOKEN (NFT) MARKETING STRATEGY - Chusnul Rofiah (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
The non-fungible token (NFT) issue motivates this research as it presents a great opportunity for talented creators to support creative businesses in Indonesia, increase art's exposure to local and international markets, and earn royalties for their works of art. This research focuses on how a non-fungible token (NFT) digital object can be sold out and what strategy is used to sell the NFT? using a cyberphenomenology approach. Informant criteria: The informant must have sold NFTs at least three times themselves. Have a minimum of 1000 followers on social media and one year of experience. The focus areas for online media research include Facebook, Instagram, and the Indonesian NFT community. We collected the data through in-depth media interviews, direct observation of social media, and manual data analysis procedures, which involved triangulating sources and theories. The findings indicate that the NFT marketing strategy involves SFS, consistent promotion, regular product posting, Twitter retweets, targeting a specific market, and celebrity endorsement. The price of a resale product is typically higher than its original price. NFT products are animations. GIFs are difficult to steal. Products are animated GIFs. Marketplace (Opensea): NFTs are a source of income. Direct transfers of NFTs are possible without the need for purchase transactions. Cryptocurrency: Smart Contract System: Low Crypto Prices NFTs will end.